Literature Review: Analysis of Coastal Vulnerability and Comprehensive Adaptation Strategies in Padang City, West Sumatra - Midratul Fardilla; Ilham Salsabila; Zeus Marullah Aswin; Eni Kamal; Abdul Razak; Widya Prarikeslan; Mhd. Ridha (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Coastal areas in Indonesia, including Padang City, face increasing vulnerability due to a combination of natural processes and human activities. This literature review synthesizes findings from various studies to assess the dimensions of coastal vulnerability and adaptation strategies, with a focus on Padang City, West Sumatra. The review reveals that major issues include abrasion, seawater intrusion, tidal flooding, ecosystem degradation, and limited adaptive capacity of coastal communities. Physical vulnerability is influenced by factors such as building density, land subsidence, ecosystem degradation, and inadequate adaptive infrastructure, while socio-economic and institutional challenges include weak governance, limited funding, and low community participation. Studies in different regions demonstrate that effective adaptation requires a combination of physical engineering, ecosystem-based approaches, socio-economic diversification, and institutional integration. For Padang City, the high exposure to coastal hazards, coupled with dependence on marine-based livelihoods, underscores the urgency of comprehensive adaptation strategies. These strategies should be proactive, data-driven, and involve cross-sector collaboration, integrating coastal vulnerability assessments into urban planning, policy frameworks, and community capacity-building efforts. Without such integrated approaches, Padang faces escalating risks to its environmental sustainability, socio-economic resilience, and long-term development.